Analysis Financial Performance of Regional Government in Bengkulu Province - Rara Mianti; Fachruzzaman Fachruzzaman (Faculty of Economics and Business, Universitas Malikussaleh, 2020)
This research is using quantitative approach which aims to determine whether there are differences in the area ratio based on fiscal decentralization ratio of local financial, local financial dependency ratio, the ratio of the area of financial independence, effectiveness ratio , the ratio of growth ( growth) PAD , the ratio ( share) of revenue over the last ten years . By using the entire sample of local governments as Bengkulu province which is not an expansion of the area during the study period from 1995 to 2012 .That the government of Bengkulu , South Bengkulu , North Bengkulu , Rejang Lebong . Testing the hypothesis in this study was conducted with two analytical tools are paired sample t - test and Wilcoxon signed ranks test using SPSS analysis tool using a significant level of 0.025 % . The results of these tests indicate that there is significantly different as the local government 's financial performance during the period of Bengkulu province last ten years , well after the implementation of regional autonomy and after the economic crisis .